Intestinal permeability in strongyloidiasis - Werneck-Silva,A.L. (2001)
The objective of the present study was to assess intestinal permeability in patients with infection caused by Strongyloides stercoralis. Twenty-six patients (16 women and 10 men), mean age 45.9, with a diagnosis of strongyloidiasis were evaluated. For comparison, 25 healthy volunteers (18 women and 7 men), mean age 44.9, without digestive disorders or intestinal parasites served as normal controls. Intestinal permeability was measured on the basis of urinary radioactivity levels during the 24 h following oral administration of chromium-labeled ethylenediaminetetraacetic acid (51Cr-EDTA) expressed as percentage of the ingested dose. The urinary excretion of 51Cr-EDTA was significantly reduced in patients with strongyloidiasis compared to controls (1.60 ± 0.74 and 3.10 ± 1.40, respectively, P = 0.0001). Intestinal permeability is diminished in strongyloidiasis. Abnormalities in mucus secretion and intestinal motility and loss of macromolecules could explain the impaired intestinal permeability.